A case study of the 9 August 1988 South Atlantic storm: Numerical simulations of the wave activity - Innocentini, Valdir [UNESP]; Caetano Neto, Ernesto dos Santos [UNESP] (American Meteorological Society, 1996)
During 9-11 August 1988, a cyclone developed over Uruguay in the lee of the Andes Mountains and moved over the South Atlantic Ocean, where it redeveloped into an intense storm. This storm was responsible for unusual wave activity along the Brazilian shoreline from 22° to 32°S. The Brazilian news media reported the loss of at least one life, waves of 3 m and higher, and the disappearance of a drainage pipe, which weighed 8000 kg, off the shores of Rio de Janeiro. In this paper, the evolution of this intense storm and the associated ocean wave response is studied through European Centre for Medium-Range Weather Forecasts analyses, a hydrostatic limited-area meteorological model, and a second-generation prognostic wave model. The atmospheric model results indicated the presence of a long-lived and large fetch with surface wind velocities higher than 12 m s -1 directed toward the coast. Some areas with velocities of 20 m s -1 were embedded in the fetch. The wave model forced by this wind field was able to simulate waves with a significant height of 8 m far from the coast and about 4 m in regions very close to the Brazilian coast in agreement with the occurrence reported at Rio de Janeiro. The swell propagation toward the coast of Rio de Janeiro was obstructed by a northeastward 10-m wind during the first 24-h period of the model's integration. During the second 24-h period, the fetch was still large and strong, but the obstacle was removed by a counterclockwise rotation of wind direction favoring the swell and windsea propagation toward the Rio de Janeiro coast.
Keywords: numerical simulations; storms; wave forecasting; Atlantic, (South); Simulation-Numerical; South Atlantic; Storms; Waves